Development of a pelvic floor evaluation device - Jittima Manonai (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To validate the device and investigate the effect of this device on symptoms, quality of life, and pelvic floor muscle strength. Material and Method: The device was designed to measure vaginal pressure changes using air-pressure balloon and abdominal wall muscle activities using surface electromyography. To test the accuracy of the device, for vaginal pressure measurement, a Mercury sphygmomanometer was used as a gold standard, and for abdominal wall muscle activity, a standard biofeedback machine was used as a reference device. A randomized, controlled trial was conducted in sixty-one women with stress urinary incontinence. They were randomly divided into two groups undergoing PFMT with a single 15-minute biofeedback session (BF + PFMT group) or without biofeedback (PFMT group). The pelvic floor muscle strength, abdominal wall muscle activity and incontinence-specific quality of life questionnaire (I-QOL), measurements were evaluated at baseline and at 8- and 16-week after treatment. Results: The accuracy of vaginal probe pressure perineometry was 98% compared to a standard sphygmomanometer. The device could detect abdominal wall muscles activities at 10 milliseconds (100 Hz), 20 milliseconds (50 Hz), and 50 milliseconds (20 Hz). After 8 and 16 weeks of treatment, there were statistically significant intra-group differences in the maximum vaginal squeeze pressure in both groups. However, the inter-group differences were not demonstrated. The proportion of women who performed pelvic floor muscle exercise correctly was significantly higher in the BF + PFMT group (72.41%) compared to the PFMT group (21.88%) at week 16 (p<0.05). Conclusion: The simple pelvic floor muscle strength evaluation device might be helpful in pelvic floor muscle training in a low resource setting.